Knowledge, Attitude and Practice Regarding Biomedical Waste Management Among The Health Care Workers In Hospitals Of Bikaner, Rajasthan, India - Abdul Aalim Usta; Imran Khan Pathan; Mohammad Asif (Asia Pacific Journal of Health Management)
Objective: To estimate the Knowledge, Attitude and Practice (KAP) with regarding to bio-medical waste management among the healthcare workers in hospitals of Bikaner district.